Biochemical Pattern of Methylmalonyl-CoA Epimerase Deficiency Identified in Newborn Screening: A Case Report - Evelina Maines; Roberto Franceschi; Francesca Rivieri; Giovanni Piccoli; Björn Schulte; Jessica Hoffmann; Andrea Bordugo; Giulia Rodella; Francesca Teofoli; Monica Vincenzi; Massimo Soffiati; Marta Camilot (International Journal of Neonatal Screening)
Methylmalonyl-CoA epimerase enzyme (MCEE) is responsible for catalyzing the isomeric conversion between D- and L-methylmalonyl-CoA, an intermediate along the conversion of propionyl-CoA to succinyl-CoA. A dedicated test for MCEE deficiency is not included in the newborn screening (NBS) panels but it can be incidentally identified when investigating methylmalonic acidemia and propionic acidemia. Here, we report for the first time the biochemical description of a case detected by NBS. The NBS results showed increased levels of propionylcarnitine (C3) and 2-methylcitric acid (MCA), while methylmalonic acid (MMA) and homocysteine (Hcy) were within the reference limits. Confirmatory analyses revealed altered levels of metabolites, including MCA and MMA, suggesting a block in the propionate degradation pathway. The analysis of methylmalonic pathway genes by next-generation sequencing (NGS) allowed the identification of the known homozygous nonsense variation c.139C>T (p.R47X) in exon 2 of the MCE gene. Conclusions: Elevated concentrations of C3 with a slight increase in MCA and normal MMA and Hcy during NBS should prompt the consideration of MCEE deficiency in differential diagnosis. Increased MMA levels may be negligible at NBS as they may reach relevant values beyond the first days of life and thus could be identified only in confirmatory analyses.